Inclusão da criança com autismo na educação física escolar - Garozzi, Gabriel Vighini (2020)
In the search to build a more inclusive, attentive and welcoming Physical Education to the different subjects who attend the school space and who are entitled to free, quality public education, this study aims to understand the inclusion process of a child with autism in school Physical Education classes. For that, it establishes two specific objectives: a) to analyze the development path of a child with autism at different moments of the Physical Education class; and b) to identify the pedagogical strategies adopted by the teacher to enable the insertion, permanence and learning of a child with autism in Physical Education classes. It is a qualitative research, configuring itself as an ethnographic case study. The historical-cultural approach made up the theoretical and methodological basis of this work, sharing the theoretical framework of Vigotski and his collaborators, who conceive the development of the subjects from the relationships and interactions that are provided for in the mediated processes. The subjects were a Physical Education teacher and 25 students, of both sexes, aged between seven and eight years, one with autism. All students belong to a regular class in the initial grades of elementary school, from a public school in the city of Vitória-ES. The intervention process was carried out from February to June 2019, following three weekly Physical Education classes. In addition to that moment, every Monday, the teacher and the researcher met for evaluation and planning, for an hour and thirty minutes. The information was produced and recorded using the following instruments: participant observation, filming, field diary and semi-structured interview. The procedures for analyzing the information produced occurred based on microgenetic analysis, taking into account the two moments identified by us in the analysis of the teacher's classes: a) moment of the initial conversation wheel of the class; and b) moment of experience with the content of gymnastics. At the time of the initial conversation, the results show that it is important for the teacher to establish constant communication with the student with autism, seeking to mean and give meaning to her actions in the context of the class. They indicate that the demonstration and verbal instruction were potent elements of the pedagogical work for the student to participate in the proposed activities. In addition, they point out that the fixation presented by the student with autism to objects and things of interest to him was a potential aspect to be explored in the boy's learning. At the moment of experiencing the content of gymnastics, three interesting strategies for the inclusion of students with autism in the space-time of Physical Education classes are highlighted: the reorganization of the structure of the proposed activities, favoring the supply of materials and motor actions that were in the interest of the student; the organization of the class in small groups, carrying out the activities in the form of a circuit, which enabled a closer relationship between the student and colleagues; and the systematization of a class “open to students' experiences”, which allowed the teacher to act closer to the student with autism and to other students. From the reflections made, we understand that, in order to carry out an inclusion movement in Physical Education classes, it is necessary to understand the person with disabilities/autism as a subject that is built and developed within social, cultural and historical relationships through the language and mediation of the other. Finally, it concludes that the disability itself is not responsible for tracing the individual's destiny, but the way in which the social environment understands and highlights (or not) the deficit is what will define its possibilities of education and development.